Criminal Law Policy About Monetary Sanction In The Bill of Penal Code OF Indonesia - Yoserwan Yoserwan; Elwi Danil; Iwan Kurniawan (Simbur Cahaya, 2020)
Criminal law policy about criminal punishment is one of the most important substances in Criminal law making and reform. Even, the regulation of criminal punishment is assumed as one of indicators in measuring the development and civilization of a nation.  The current Penal Code of Indonesia (PCI) or KUHP that is the heritage of Dutch colonial is much influenced by Classical School and placed imprisonment as priority.  The consequence is that in one hand the high rate of imprisonment and over-capacity in the prison on the other hand. Such a condition will result in problems such as the diffulties conducting rehabilitation and providing the budgeting.  In its development, modern criminal law, especially from the the idea of utilitariansme, tries to find various alternatives to imprisonment, especially Monetary Punishment.  Even though PCI has adopted regulation on monetary punishment, the existing system still places imprisonment very dominant.  The Indonesian legislator which is currently hearing the Bill of PCI to replace the current PCI should foster the function of monetary punishment so that it results in the utility for the people. This article is discussing about how criminal law policy   about the monetary punishment regulated in Bill of PCI.  This study applies normative legal research and put stressing in (content analysis). The result of this study shoes that Bill of PCI has not yet placed monetary punishment as first priority in criminal punishment. There are some regulations that make it is not possible for monetary punishment is more selected in criminal enforcement. Therefore, Bill of PCI should be more accommodative in optimizing financial punishment in   realizing criminal punishment for the benefit of the people.